2015
DOI: 10.2961/jlmn.2015.01.0006
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Micro-Raman Measurement of Temperature Dynamics during High-Repetition-Rate Ultrafast Laser Microprocessing

Abstract: High power ultrafast lasers are nowadays able to provide high ablation rates and meet the technical requirements and performances needed for many industrial applications. However depositing more energy into the target may induce heat accumulation, and consequently enhances the ablation efficiency as well as introduces some detrimental effect on the processing quality. So, the key issue is to improve throughput while maintaining the processing quality and preventing from any deformation of the work piece. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fig. 8 shows their result of the measured temperature distribution [72]. Within the range of 73 mm from the focus of the processing pulse, they described that it was difficult to measure temperature due to the onset of large background signals, as shown in the inset of Fig.…”
Section: Temperature Dynamicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Fig. 8 shows their result of the measured temperature distribution [72]. Within the range of 73 mm from the focus of the processing pulse, they described that it was difficult to measure temperature due to the onset of large background signals, as shown in the inset of Fig.…”
Section: Temperature Dynamicsmentioning
confidence: 95%
“…On the other hand, high-repetition ultrafast laser pulses can induce smooth modifications at a high speed [8][9][10]. Hashimoto et al measured the temperature dynamics inside glass by time-resolved micro-Raman spectroscopy during high-repetition-rate ultrafast laser microprocessing [72]. It has been shown that temperature dynamics is quite important because the processed area is strongly influenced by the heat accumulation effect.…”
Section: Mechanism Of Ultrafast Laser Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting modifications range from isotropic refractive index changes, 3 artificial birefringence due to so-called nanogratings 4,5 to microscopic voids due to a confined microexplosion. 7,8 After rapid cooling (typical cooling rates >10 6 K/s), the molten glass resolidifies, allowing for the local bonding of glass interfaces with high stability. 7,8 After rapid cooling (typical cooling rates >10 6 K/s), the molten glass resolidifies, allowing for the local bonding of glass interfaces with high stability.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, when using high repetition rates, the laser pulses act as a local heat source, leading to temperatures well above the melting temperature of the glass. 7,8 After rapid cooling (typical cooling rates >10 6 K/s), the molten glass resolidifies, allowing for the local bonding of glass interfaces with high stability. 9 Based on the confined transfer of heat, even different glass combinations can be successfully bonded together.…”
Section: Introductionmentioning
confidence: 99%